The Relationship of Family Support with The Practice of Breast Examination (Breast Examination) an Adolescent Women at High School 17 Batam, Batam City, Riau Islands Province, 2021 - Aminah Aatinaa Adhyatma; Siti Nurlela (UIMA Press, 2021)
Background: Breast cancer is usually experienced by women of childbearing age over 35 years, but now it has undergone a shift and is starting to be experienced by teenagers. Prevention that can be done to detect breast cancer early is by Breast Self-Examination (BSE). Objectives: This study aims to analyze the relationship between family support and the practice of Self-Breast Examination (BSE) in adolescent girls at High School 17 Batam. Methods: The research was conducted at High School 17 Batam. In this study, an analytical design with a Cross Sectional approach was used in April 2021 for Young Women. The sample in this study amounted to 77 respondents using total sampling technique. Collecting data using a questionnaire. The statistical test used was the Chi Square Test to analyze the relationship between family support and the practice of Breast Self-Examination (BSE). Results: The results showed that there was a significant relationship between family support and the practice of Breast Self-Examination (BSE) (p value <0.05). Conclusion: There is a relationship between family support and the practice of Breast Self-Examination (BSE). It is hoped that the breadth of access to information media can add insight to respondents and their families, especially parents, to be able to play a role in providing support related to Breast Self-Examination (BSE).